ACTIVITY-BASED COSTING SYSTEM GENERATIONS: A LITERATURE REVIEW - Zainab Jaafar Salman AL-hilaly (Scholars Digest Publishing, 2024)
Economic units today operate in an industrial environment characterized by complexity and intense competition to create and maintain the fundamental success factors, which are quality, cost, and price, as well as innovation, specifications, and time. Cost is one of the factors in enhancing the competitiveness between companies, so attention must be paid continuously to methods of measuring them accurately and objectively, and this requires transformation from the traditional cost accounting systems that rely on a single basis for charging products with their costs (particularly indirect) to the modern systems that deal with the real and direct cause of the cost occurrence, the activity-based costing system emerged that determined the relationship between activity and cost, but because of the weaknesses that accompanied the application of this system The most important of which is the high cost of applying it, its consumption of a long time and many resources, the interest in the internal causes of cost (the activities necessary for production) and its neglect of the external causes of cost (the specifications that the customer desires in the product), has led some to think about developing the ABC system. The current article aims to trace the path of the ABC system in light of the stages of development of its successive generations by defining the philosophy and steps for applying each generation, while indicating the advantages and disadvantages that appeared when applying those generations.
Keywords: ABC activity-based costing system, ABCII specification-based costing system, ABCM activity-based cost management system, TDABC time-oriented activity-based costing system, PFABC performance-based activity-based costing system.